Targeting rare and non-canonical driver variants in NSCLC: an uncharted clinical field - Volckmar, Anna-Lena; Christopoulos, Petros; Kirchner, Martina; Allgäuer, Michael; Neumann, Olaf; Budczies, Jan; Rempel, Eugen; Horak, Peter; Glade, Julia; Goldschmid, Hannah; Şeker-Cin, Huriye; Brandt, Regine; et al. (Lung cancer, 2021)
Objectives - Implementation of tyrosine kinase inhibitors (TKI) and other targeted therapies was a main advance in thoracic oncology with survival gains ranging from several months to years for non-small-cell lung cancer (NSCLC) patients. High-throughput comprehensive molecular profiling is of key importance to identify patients that can potentially benefit from these novel treatments. - Material and Methods - Next-generation sequencing (NGS) was performed on 4500 consecutive formalin-fixed, paraffin-embedded specimens of advanced NSCLC (n=4172 patients) after automated extraction of DNA and RNA for parallel detection of mutations and gene fusions, respectively. - Results and Conclusion - Besides the 24.9 % (n=1040) of cases eligible for approved targeted therapies based on the presence of canonical alterations in EGFR exons 18-21, BRAF, ROS1, ALK, NTRK, and RET, an additional n=1260 patients (30.2 %) displayed rare or non-canonical mutations in EGFR (n=748), BRAF (n=135), ERBB2 (n=30), KIT (n=32), PIK3CA (n=221), and CTNNB1 (n=94), for which targeted therapies could also be potentially effective. A systematic literature search in conjunction with in silico evaluation identified n=232 (5.5 %) patients, for which a trial of targeted treatment would be warranted according to available evidence (NCT level 1, i.e. published data showing efficacy in the same tumor entity). In conclusion, a sizeable fraction of NSCLC patients harbors rare or non-canonical alterations that may be associated with clinical benefit from currently available targeted drugs. Systematic identification and individualized management of these cases can expand applicability of precision oncology in NSCLC and extend clinical gain from established molecular targets. These results can also inform clinical trials.